History of the Philippines economic, social, political - Benitez, Conrado 1889- (Ginn and Co., 1940)
Research and thorough-going scholarship, in general, are the basic elements that underlie the proper development of history, science, and literature. There can really be no academic progress where these two essentials are wanting. Historical or literary works carry the stamp of permanence when they are the products of both. We must develop these two motivating forces among our men of letters that we may have worthy contributions to Filipino intellectual advancement.